Roughness of dental implants: comparative analysis of reuse of acids in surface treatment - Mendes, Giovanna Nascimento; Takeshita, Wilton Mitsunari [UNESP]; Trento, Cleverson Luciano (FapUNIFESP (SciELO), 2023)
Introduction: The importance of roughness for osseointegration is due to the configuration of proteins with the surface of the implant, and adsorption. Different methods are used in surface treatments, in which parts of the surface layer are removed, such as acid attack. Objective: To analyze changes in roughness on the surface of osseointegrated implants treated by double acid etching with single-use and up to 4 reuses of serums at a magnification of 500x, 1000x, 2000x, and 4000x in the scanning microscope (SEM). Method: Samples of adherent implants (SINGULAR Implants ®) of lever alloy (n=10) were subdivided into 5 groups: control, treatment 1, 2, 3, and 4, according to the reuses. For the surface topography of the samples, SEM was used, followed by analysis by Image J software. Using the ANOVA test and Turkeys post-test, Ra and Rq values were statistically analyzed. Result: The data obtained both by the images captured in the SEM and by the Ra and Rq numbers acquired by the Image J illustrate that the treatment with the double acid attack with 5 uses of the same ones served, was positive for the surface treatment of the alloy implant of independent. Conclusion: It can be concluded that up to four reuses of food do not statistically interfere with roughness values. More studies are needed regarding the reuse of acids, certainly to reduce costs to manufacturers, increasing sustainability while maintaining product quality.
Rugosidade dos implantes dentários: análise comparativa da reutilização de ácidos no tratamento de superfície
Keywords: dental implants; metalmechanic industry; Surface properties